Upper respiratory symptoms (URS) and salivary responses across a season in youth soccer players: A useful and non-invasive approach associated to URS susceptibility and occurrence in young athletes - Lopes, Renata Fiedler; Minuzzi, Luciele Guerra [UNESP]; Figueiredo, Antonio Jose; Goncalves, Carlos; Tessitore, Antonio; Capranica, Laura; Teixeira, Ana Maria; Rama, Luis (Public Library Science, 2020)
This study examined the effect of a competitive season on salivary responses [cortisol (sC), testosterone (sT), Testosterone/Cortisol ratio (sT/C), Immunoglobulin A (sIgA), sIgA secretion rate (srIgA), alpha-amylase (sAA)] and upper respiratory symptoms (URS) occurrence in three teams of male soccer players (Under-15, Under-17 and Under-19 yrs.). Training and competition volumes, salivary biomarkers and URS were determined monthly. No differences were found for monthly training volume between teams. Incidence of URS was higher for the U15 (44.9% of the total cases). Higher sT and srIgA were observed for the U19, lower sC were found for the U17 and sAA showed higher values for the U15 throughout the season. In the U15, significant difference (p= .023) was found for sIgA concentration with higher concentration values in January compared to December (-42.7%;p= .008) and the sT showed seasonal variation (p< .001) with the highest value in January significantly different from October (-40.2%;p= .035), November (-38.5%;p= 0.022) and December (-51.6%;p= .008). The U19 presented an increase in sC in March compared to February (-66.1%,p= .018), sT/C were higher in February compared to March (-58.1%;p= .022) and sAA increased in March compared to September (-20.5%;p= .037). Negative correlations, controlled for age group, were found between URS occurrence and srIgA (r = -0.170, p = .001), sAA (r = -0.179, p = .001) and sT (r = -0.107, p = .047). Monitoring salivary biomarkers provides information on mucosal immunity with impact in URS occurrence. Coaches could manipulate training loads to attenuate the physical stressors imposed on athletes, especially at demanding and stressful periods.